Adrenal sparing giant adrenal cyst excision by 3D laparoscopic approach: a case report - Patankar, Suresh B.; Padasalagi, Gururaj R.; Thakare, Kashinath V.; Narkhede, Mayur M. (International Journal of Research in Medical Sciences, 2023)
Adrenal cyst is rare clinical entity. Usually they are asymptomatic, non-functional, <10 cm in size and often discovered incidentally. We report a left adrenal cyst in 58-year-old woman measuring 23 cm in diameter, displacing left kidney infero-medially and pancreas anteriorly, because of its huge size. She presented with left flank pain over a 6-month period. Serial abdominal ultrasound and CT imaging revealed left suprarenal cystic mass of size 10 cm to begin with and gradually increased to size of 23 cm over period of 10 years when she became symptomatic. All laboratory and endocrine function tests were normal. 3D laparoscopic surgery done and cyst was completely removed with preservation of adrenal gland. Histopathological examination revealed a benign endothelial adrenal cyst. The postoperative course was uneventful and patient had no evidence of recurrence during follow-up. The giant adrenal cysts are relatively rare and represent great surgical challenge during resection.